Exercise, Sedentary Pastimes, and Cognitive Performance in Healthy Older Adults. (May 2015) - Steinberg, Susanne Inez; Sammel, Mary Dupuis; Harel, Brian Tal; Schembri, Adrian; Policastro, Christopher; Bogner, Hillary R.; Negash, Selamawit; Arnold, Steven Edward
Background: Moderately vigorous physical activity (MVPA) provides a protective affect against cognitive decline and cardiovascular risk factors. Less is known about sedentary pastimes or non exercise physical activity (NEPA) and cognitive performance. Method: 125 healthy adults 65 or older with no clinical evidence of cognitive impairment were enrolled. The CogState computerized neurocognitive battery was administered. Leisure activities were measured using the Community Health Activity Program for Seniors (CHAMPS). Results: Sedentary pastimes were associated with executive dysfunction ( P = 0.01); MVPA with high memory scores ( P = 0.05) and NEPA with improved working memory ( P = 0.05). Only sedentary pastimes and executive dysfunction retained significance after correction for multiple comparisons. Smoking and alcohol confounded the association of memory with sedentary pastimes and MVPA. Conclusions: Study highlights: negative impact of sedentary pastimes on executive function, need for additional investigation of sedentary behavior, NEPA, the impact of addictions upon activity in late life.